Defining the Extracellular Matrix of Rhabdomyosarcoma - Lian, Xiaolei; Bond, J. Steffan; Bharathy, Narendra; Boudko, Sergei P.; Pokidysheva, Elena; Shern, Jack F.; Lathara, Melvin; Sasaki, Takako; Settelmeyer, Teagan; Cleary, Megan M.; Bajwa, Ayeza; Srinivasa, Ganapati; et al. (Frontiers in Oncology, 2021)
Introduction: Rhabdomyosarcoma (RMS) is the most common soft-tissue sarcoma of childhood with a propensity to metastasize. Current treatment for patients with RMS includes conventional systemic chemotherapy, radiation therapy and surgical resection; nevertheless, little to no improvement in long term survival has been achieved in decades – underlining the need for target discovery and new therapeutic approaches to targeting tumor cells or the tumor microenvironment. Methods: To evaluate cross-species sarcoma extracellular matrix production, we have used murine models which feature knowledge of the myogenic cell-of-origin. With focus on the RMS/undifferentiated pleomorphic sarcoma (UPS) continuum, we have constructed tissue microarrays of 48 murine and 4 human sarcomas to analyze expression of 7 different collagens, fibrillins and collagen-modifying proteins, with cross-correlation to RNA deep sequencing. Results: We have uncovered that RMS produces increased expression of type XVIII collagen alpha 1 (COL18A1), which is clinically associated with decreased long-term survival. We have also identified significantly increased RNA expression of COL4A1, FBN2, PLOD1 and PLOD2 in human RMS relative to normal skeletal muscle. Conclusion: These results complement recent studies investigating whether soft tissue sarcomas utilize collagens, fibrillins and collagen-modifying enzymes to alter the structural integrity of surrounding host extracellular matrix/collagen quaternary structure resulting in improved ability to improve the ability to invade regionally and metastasize, for which therapeutic targeting is possible.